(untitled) (Biological Sciences - PJSIR, 1997)
Optimum conditions for the extraction and precipitation of bovine pepsin from young buffalo were studied. Changes in pH, temperature and extraction time significantly affected the extraction of pepsin. Maximum pepsin activity (222 unitsg’) was observed when minced gastric tissues were suspended in acidic solution of pH 2.2 at 40°C for 18hr. Pepsin was precipitated from the extract by adding sodium chloride at the rate of 200g·l . Pepsin activity in camel, cow, buffalo and chicken gastric tissues, under these conditions was found to be 10I, 141, 190and 222 units respectively, while 172unitsg’ pepsin activity was observed incases of sheep and goat.These gastric tissue samples of different animals were kept at _10°Cfor six months and a gradual decrease in pepsin activity by 18-68% was observed during storage.